The Relationship Between Unemployment and Economic Growth in OECD Countries: Panel Causality Test - Aydın, Elçin Karaş (My University, 2020)
Unemployment and economic growth unemployment are the most important determinants for theeconomic success of countries. Therefore, economic growth and unemployment problems are seen as importantproblems that have been continuing from past to present. Many policies have been implemented in order toreduce unemployment rate. Among these, the most important policy is to increase economic growth. Okun'slaw, which is a generally accepted theory, also supports this view. According to Okun's law, a lowunemployment rate stands out in the years with a high growth rate. In the years with a low economic growthrate, a high unemployment rate emerges. This study analyzes the relationship between unemployment rate andeconomic growth in 10 OECD countries. The study covers the period between 1969-2018. The data used inthe research were derived the OECD-Stat database. The relationship between the variables was analysedthrough the panel causality test developed by Konya (2006). This test simultaneously considers the problemsof cross-sectional dependency and slope heterogeneity among countries. A one-way causality relationship fromeconomic growth to unemployment rate was determined in Canada, Denmark, France, Greece and Turkey inthe result of panel bootstrap causality test developed by Konya (2006). In Australia, Canada, France, Greece,Korea, Netherlands, Sweden, Turkey and UK, a one-way causality relationship from unemployment rate toeconomic growth was found. In addition, a two-way causality relationship was detected betweenunemployment and economic growth in Canada, France, Greece and Turkey.
Keywords: İşletme; İktisat; İstatistik ve Olasılık